COVID as Shock Doctrine - Caamaño López, Alejandro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of this research is to investigate, from an interdisciplinary perspective between sociology, psychology, law and history, the management of the coronavirus crisis, which in the Spanish case is based on authoritarian lounge dure logics rooted in the XIX and absolutism. With the use of measures imposed by the authorities and assumed by a terrified citizenry, governments and the media have generated a turning point that has dismantled the associative fabric and the social movements that emerged in response to the bursting of the real estate bubble that occurred in Spain.